2015
DOI: 10.1371/journal.pone.0133007
|View full text |Cite
|
Sign up to set email alerts
|

Playgroup Participation and Social Support Outcomes for Mothers of Young Children: A Longitudinal Cohort Study

Abstract: ObjectiveThis study aimed to examine friendship networks and social support outcomes for mothers according to patterns of playgroup participation.MethodsData from the Longitudinal Study of Australian Children were used to examine the extent to which patterns of playgroup participation across the ages of 3–19 months (Wave 1) and 2–3 years (Wave 2) were associated with social support outcomes for mothers at Wave 3 (4–5 years) and four years later at Wave 5 (8–9 years). Analyses were adjusted for initial friendsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 30 publications
1
39
0
Order By: Relevance
“…4 Results of quantitative studies of playgroup participation have shown associations with positive social and emotional development for children 5 and social support for parents. 6 This is relevant to health promotion, given the groundswell of evidence for the importance of social support for both physical and mental well being. 7 Playgroups can also be good settings for the successful health promotion of maternal physical activity interventions.…”
Section: Introductionmentioning
confidence: 99%
“…4 Results of quantitative studies of playgroup participation have shown associations with positive social and emotional development for children 5 and social support for parents. 6 This is relevant to health promotion, given the groundswell of evidence for the importance of social support for both physical and mental well being. 7 Playgroups can also be good settings for the successful health promotion of maternal physical activity interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Families experiencing disadvantage have been overrepresented in reports of low fruit and vegetable consumption, reliance on sweet drinks and snacks, concerns about risks of active play and confusion about the role of electronic screen use for language development and education . Key messages promoting child health may be new to parents not attending the scheduled MCH visits, ‘new parent’ groups or other health services …”
Section: Discussionmentioning
confidence: 94%
“…Non-randomized evaluations of playgroups in Australia have also found positive effects on measures of school readiness (Gregory et al 2016, Hancock et al 2015. To our knowledge, our evaluation is the first randomized evaluation of play-based activities that are "community-led" in the sense that the activities are supported by community leaders and all participants including facilitators are community volunteers.…”
Section: Introductionmentioning
confidence: 87%